QKD system with fast active optical path length compensation - Park, Byung Kwon; Lee, Min Soo; Woo, Min Ki; Kim, Yong-Su; Han, Sang-Wook; Moon, Sung (SCIENCE PRESS, 2017)
We develop a quantum key distribution (QKD) system with fast active optical path length compensation. A rapid and reliable active optical path length compensation scheme is proposed and applied to a plug-and-play QKD system. The system monitors changes in key rates and controls it is own operation automatically. The system achieves its optimal performance within three seconds of operation, which includes a sifted key rate of 5.5 kbps and a quantum bit error rate of less than 2% after an abrupt temperature variation along the 25 km quantum channel. The system also operates well over a 24 h period while completing more than 60 active optical path length compensations.
Keywords: QUANTUM KEY DISTRIBUTION; FIELD-TEST; DISTRIBUTION NETWORK; CRYPTOGRAPHY; FIBER; PLUG; AREA